2020
DOI: 10.1177/2041731420947242
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammatory microenvironment using a self-healing hydrogel loaded with BM-MSCs for advanced wound healing in rat diabetic foot ulcers

Abstract: A diabetic foot ulcer (DFUs) is a state of prolonged chronic inflammation, which can result in amputation. Different from normal skin wounds, various commercially available dressings have not sufficiently improved the healing of DFUs. In this study, a novel self-healing hydrogel was prepared by in situ crosslinking of N-carboxyethyl chitosan ( N-chitosan) and adipic acid dihydrazide (ADH) with hyaluronic acid-aldehyde (HA-ALD), to provide a moist and inflammatory relief environment to promote stem cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 56 publications
0
72
0
Order By: Relevance
“…Another approach to increase growth factors is to provide bone-marrow mesenchymal stem cells (BM-MSCs). Bai et al developed an injectable hydrogel made from crosslinking N-chitosan and adipic acid dihydrazide with hyaluronic acid-aldehyde to deliver BM-MSCs into the wound bed (250). In vitro and in vivo investigations in diabetic wound healing showed that the hydrogel was able to stimulate BM-MSC-derived secretion of TGF-b1, VEGF, and FGF-2 as well as inhibiting chronic inflammation through M2 macrophage polarization (250).…”
Section: Targeting Inflammatory Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Another approach to increase growth factors is to provide bone-marrow mesenchymal stem cells (BM-MSCs). Bai et al developed an injectable hydrogel made from crosslinking N-chitosan and adipic acid dihydrazide with hyaluronic acid-aldehyde to deliver BM-MSCs into the wound bed (250). In vitro and in vivo investigations in diabetic wound healing showed that the hydrogel was able to stimulate BM-MSC-derived secretion of TGF-b1, VEGF, and FGF-2 as well as inhibiting chronic inflammation through M2 macrophage polarization (250).…”
Section: Targeting Inflammatory Balancementioning
confidence: 99%
“…Bai et al developed an injectable hydrogel made from crosslinking N-chitosan and adipic acid dihydrazide with hyaluronic acid-aldehyde to deliver BM-MSCs into the wound bed (250). In vitro and in vivo investigations in diabetic wound healing showed that the hydrogel was able to stimulate BM-MSC-derived secretion of TGF-b1, VEGF, and FGF-2 as well as inhibiting chronic inflammation through M2 macrophage polarization (250). It also induced granulation tissue formation, collagen deposition, tissue vascularization, and improved wound closure (250).…”
Section: Targeting Inflammatory Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged inflammation is the ultimate cause of delayed DW healing [ 71 ]. One of the key bioactivities features desired for an active wound dressing is the anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSC) is widely used as seed cells in tissue engineering and regenerative medicine [10]. A series of researches have indicated that BMSC have great potential for enhancing the repair of bone defects, owing to its high capacity for self-renewal and multi differentiation potential.…”
Section: Introductionmentioning
confidence: 99%